Effect of cooking on the total oxalate content on taro (Colacasia esculenta L. Schott) - Cachuela, Joan Maris S.; Francisco, Ma. Leonora dL. (Quezon City College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT The oxalates present in taro are said to be of some concern because of the several health risk factors it poses. The objective of the study was to determine and evaluate the effect of various cooking methods on the oxalate content of locally cultivated Colocasia esculenta L. Schott cormels. Taro cormels were subjected to six different treatments namely boiling, steaming, baking, grilling, frying, and steeping for 20 min. Samples were withdrawn at 5 min intervals to determine total oxalate content using the digestion-precipitation-titration method. A mean of 264 mg/100g FW total oxalate was determined for the raw taro. Statistical analysis using Analysis of Variance technique (P≤O.O5) and the Tukey?s test revealed a non-significant decrease in total oxalate during steeping while significant reduction was observed during moist heating (boiling and steaming) after 15 and 10 min of cooking respectively, with boiling effecting the highest oxalate reduction (78% in 20 min). Dry heat methods such as baking and grilling significantly increased the oxalate content after 10 min of cooking. Frying significantly decreased the oxalate content after 10 min of cooking. Regression analysis revealed that boiling, baking, and grilling followed a zero-order reaction while frying followed a first order reaction. The results imply that locally cultivated Colocasia esculenta L. Schott cormels are high in total oxalates but simple cooking methods such as boiling, steaming and frying can readily decrease the amount, thereby decreasing health related problems.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Cookery (Taro); Taro leaves -- Composition